“Sistema de gestión de proyectos para el departamento de investigación de la Universidad Técnica de Cotopaxi Extensión La Maná”. - Benites Guerra, Nelly Shirley (2023)
At the Technical University of Cotopaxi, La Maná extension, research projects are developed in the Research Department where the main participants are the career coordinators in charge of carrying out and presenting all the documentation of the research carried out to the person in charge of the research area for their respective review. and publication so that students, professionals and researchers can view through the project management system. Therefore, the information system is developed that allows contributing to the university by automating the necessary processes so that the coordinators can be approved for the projects of the different categories. For which it was necessary the bibliographical investigation that facilitate the reference and guide for the development of the system; also, with the technique of research instruments such as the interview and survey to establish the functional requirements for the development of the project management system through the agile Scrum methodology. Finally, the results of the research based on the scientific point of view are included, presenting the diagnosis of the black box and white box tests, opening the implementation of the system on the web for the use of project management in the research department. UTC La Mana.